Measuring Patient Safety Climate in Acute Stroke Therapy - Bohmann, Ferdinand O.; Guenther, Joachim; Gruber, Katharina; Manser, Tanja; Steinmetz, Helmuth; Pfeilschifter, Waltraud (Frontiers in Neurology, 2021)
Background: Treatment of acute stroke is highly time-dependent and performed by a multiprofessional, interdisciplinary team. Interface problems are expectable and issues relevant to patient safety are omnipresent. The Safety Attitudes Questionnaire (SAQ) is a validated and widely used instrument to measure patient safety climate. The objective of this study was to evaluate the SAQ for the first time in the context of acute stroke care. Methods: A survey was carried out during the STREAM trial (NCT 032282) at seven university hospitals in Germany from October 2017 to October 2018. The anonymous survey included 33 questions (5-point Likert scale, 1 = disagree to 5 = agree) and addressed the entire multiprofessional stroke team. Statistical analyses were used to examine psychometric properties as well as descriptive findings. Results: 164 questionnaires were completed yielding a response rate of 66.4 %. 67.7 % of respondents were physicians and 25.0 % were nurses. Confirmatory Factor Analysis revealed that the original 6-factor structure fits the data adequately. The SAQ for acute stroke care showed strong internal consistency (α = .88). Exploratory analysis revealed differences in scores on the SAQ dimensions when comparing physicians to nurses and when comparing physicians according to their duration of professional experience. Conclusions: The SAQ is a helpful and well-applicable tool to measure patient safety in acute stroke care. In comparison to other high-risk fields in medicine, patient safety climate in acute stroke care seems to be on a similar level with the potential for further improvements. Trial registration: clinicaltrials.gov Identifier: NCT032282